1962
DOI: 10.1099/00221287-28-1-181
|View full text |Cite
|
Sign up to set email alerts
|

Indifferent and Haemolytic Streptococci Possessing Group-Antigen F

Abstract: SVJhIhlARY' Indifl'erent ' strains of streptococci-j .e. strains which give no haemolysis or greening on blood-agar plates-frequently occur in cultures from dental root-canals. A scrological study of over 200 strains of these streptococci showed that about half of' them belonged to Lanceficld groups F, G or C. It was shown by cross-absorption that the group-antigen of indifferent streptococci of group F is identical with the group-antigen of haemolytic strains of group 17. .+rt from the group-antigen, five ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

1966
1966
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 1 publication
3
57
0
Order By: Relevance
“…Ottens & Winkler (1962) examined non-haemolytic streptococci from the dental root-canal, and found that a number of them possessed the Lancefield-group antigen C, F or G. These workers recognized that the non-haemolytic members of groups C and G differed from the familiar 'pyogenic' ,-haemolytic members of these groups, and also detected the type antigens of the group-F streptococcus (Bliss, 1937) in many of the non-haemolytic streptococci of the dental root-canal, whether or not a group antigen was present. Colman & Williams (1965, 1972; see also Colman, 1968) compared representative strains from Guthof (1956) and Ottens & Winkler (1962) with minute-colony forming f,-haemolytic streptococci of groups F and G (Long & Bliss, 1934;Bliss, 1937) and with the type strain of Streptococcus MG (Mirick et al 1944). They concluded that all of them should be included in the species S. milleri, but characterized it by a somewhat different set of biochemical characters from those given by Guthof (1956), by the sugar components in the cell wall, and by the frequent possession of one of a series of antigens that included the type antigens of group-F streptococci (the so-called Ottens antigens).…”
Section: Introductionmentioning
confidence: 99%
“…Ottens & Winkler (1962) examined non-haemolytic streptococci from the dental root-canal, and found that a number of them possessed the Lancefield-group antigen C, F or G. These workers recognized that the non-haemolytic members of groups C and G differed from the familiar 'pyogenic' ,-haemolytic members of these groups, and also detected the type antigens of the group-F streptococcus (Bliss, 1937) in many of the non-haemolytic streptococci of the dental root-canal, whether or not a group antigen was present. Colman & Williams (1965, 1972; see also Colman, 1968) compared representative strains from Guthof (1956) and Ottens & Winkler (1962) with minute-colony forming f,-haemolytic streptococci of groups F and G (Long & Bliss, 1934;Bliss, 1937) and with the type strain of Streptococcus MG (Mirick et al 1944). They concluded that all of them should be included in the species S. milleri, but characterized it by a somewhat different set of biochemical characters from those given by Guthof (1956), by the sugar components in the cell wall, and by the frequent possession of one of a series of antigens that included the type antigens of group-F streptococci (the so-called Ottens antigens).…”
Section: Introductionmentioning
confidence: 99%
“…The P-haemolytic strains, which joined the cluster at a below-average level of similarity, differed from the non-haemolytic strains by their inability to ferment lactose. All group-F strains except one were found within the S. milleri cluster; type-I1 and type-I11 antigens (Ottens and Winkler, 1962) were exclusively present in S. milleri strains, with the exception of NCTC10446 (group T). The characteristics of the S. milleri-like strains outlined here correspond well with other descriptions (Ottens and Winkler, 1962;Colman and Williams, 1967;Edwardsson, 1974;Mejire, 1975a;Mejire and Edwardsson, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…All group-F strains except one were found within the S. milleri cluster; type-I1 and type-I11 antigens (Ottens and Winkler, 1962) were exclusively present in S. milleri strains, with the exception of NCTC10446 (group T). The characteristics of the S. milleri-like strains outlined here correspond well with other descriptions (Ottens and Winkler, 1962;Colman and Williams, 1967;Edwardsson, 1974;Mejire, 1975a;Mejire and Edwardsson, 1975). The findings of this study are consistent with the view that streptococci resembling S. milleri in their physiological properties should be so named, even if they possess a group A, C, F or G antigen, and whether or not they are p-haemolytic (Colman andWilliams, 1967, 1972;Parker and Ball, 1976;Poole and Wilson, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations